2018
DOI: 10.1158/1538-7445.sabcs17-p6-03-05
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-03-05: Risk of needle-track seeding with serial ultrasound guided biopsies in triple negative breast cancer

Abstract: Background: Image-guided percutaneous needle biopsy of the breast is a common procedure. In breast cancer patients (pts) undergoing core biopsies and surgical resection on the same day, the rate of tumor cell displacement along the needle track has been reported to be up to 50%. However, the clinical significance of this finding in triple negative breast cancer (TNBC) patients (pts) undergoing serial biopsies while receiving neoadjuvant chemotherapy (NACT) is unknown. Here we report the incidence of needle-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We found that Yam et al [26] studied the risk of needle tract seeding in a series of patients with a TNBC (triple negative breast carcinoma) during anthracycline based NACT. 1.4% (2/144) of their patients were found to have NTM+ and were progressive after 2 cycles of anthracyclines during ultrasound follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Yam et al [26] studied the risk of needle tract seeding in a series of patients with a TNBC (triple negative breast carcinoma) during anthracycline based NACT. 1.4% (2/144) of their patients were found to have NTM+ and were progressive after 2 cycles of anthracyclines during ultrasound follow-up.…”
Section: Discussionmentioning
confidence: 99%